The provisions of the family (personal status) perspectives in Islamic jurisprudence. (Journal of the College of Basic Education, 2022)
Praise be to God, the Most High, many good and blessed praises, as befits the majesty of His countenance and the greatness of His authority.And peace be upon His Prophet Muhammad, the Seal of the Prophets and Messengers, and his family and companions altogether.... After God Almighty enabled me to write a research on the handicapped and what is related to their worship of prayer,Fasting, Zakat, and Hajj, and the jurisprudential issues that they contain, I seek the help of God and roll up my grandfather's hand in the searchabout their rulings with regard to personal status, and these papers wereI used the phrase, and arranged it as well as possible. I decided to see the most likely in many matters, for fear ofa